Government venture capital research: fake science and bad public policy. Issue 1 (2nd January 2019) - Cumming, Douglas; Johan, Sofia
ABSTRACT: We review statistical methods used to estimate the impact of crowding out of private venture capital (VC) by government VC. We review three types of failures that have plagued the VC literature and resulted in policy implications that are precisely the opposite of what the data actually indicate. The first failure involves the mistaken use of measures that give rise to country rankings where the best VC markets in the world are countries like Austria and Hungary, and the worst VC market in the world is the U.K. The second and more recent failure involves the use of data that do not predate the creation of government VC. The third type of failure involves not accounting for the nonrandom matching between entrepreneurs and government VC programs. We show that statistical inference in recent work that makes this latter mistake can give rise to remarkably incorrect conclusions; including, for example, a bizarre and clearly false inference that a market with more than 89% investment by government funds exhibits no evidence of displacement of private funds. In view of these issues, we offer suggestions for future research and raise some new questions that could guide policymakers in the future.